DETERMINAN KEPUTUSAN INVESTASI PADA PERUSAHAAN SEKTOR INFRASTRUKTUR DI BURSA EFEK INDONESIA - Jeanny, (2022)
This is a quantitative study aimed at determining and analyzing the effect on investment decisions of cash flow as defined by Cash Flow, liquidity as defined by CR, leverage as defined by DER, and profitability as defined by ROI. The population for this study is infrastructure sector companies listed on the Indonesian Stock Exchange (IDX) between 2019 and 2020. The sampling technique employed was non-probabilistic sampling with saturated samples, which resulted in the collection of 57 infrastructure companies during a two-year period, followed by the collection of 114 research sample units. In this study, data were analyzed using Microsoft Excel and hypotheses were tested using the Panel Data Regression Analysis with E-Views version 12 program with a 5% significant level (0.05). The test results indicate that (1) cash flow has a significant positive effect on investment decisions, (2) liquidity has a significant positive effect on investment decisions, (3) leverage has no effect on investment decisions, and (4) profitability has a significant positive effect on investment decisions. Keywords : Cash Flow, Liquidity, Leverage, Profitability, and Investment Decisions.